Perilaku Konsumtif Fenomena Perjudian Online Di Kalangan Mahasiswa: Studi Fenomenologi Mahasiswa Berdomisili Karawang - Taufik Hidayat Assegaf, M. Gahos; Yuni Dharta, Firdaus; Oxcygentri, Oky (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to determine the meaning and motives of students regarding online gambling and the consumer behavior experienced by them. This study uses a qualitative method with a phenomenological approach. Because in this study we want to find out a phenomenon that comes from the informant's experience directly, and also want to know the meaning and motives. The theory used in this study is Alfred Schutz's Phenomenology theory as the basis for researchers in conducting this study. The results of the study show that informants interpret consumer behavior as self-confidence, prestige, and also as a fulfillment of desire. The informants' motives are divided into because motive and in order to motive because both phases are influenced by pressure from groups and also lack of embrace from parents.